2019
DOI: 10.1037/pag0000392
|View full text |Cite
|
Sign up to set email alerts
|

Investigating core assumptions of the “American Dream”: Historical changes in how adolescents’ socioeconomic status, IQ, and GPA are related to key life outcomes in adulthood.

Abstract: The present study examines how historical changes in the U.S. socioeconomic environment in the 20th century may have affected core assumptions of the "American Dream." Specifically, the authors examined whether such changes modulated the extent to which adolescents' intelligence (IQ), their grade point average (GPA), and their parents' socioeconomic status (SES) could predict key life outcomes in adulthood about 20 years later. The data stemmed from two representative U.S. birth cohorts of 15-and 16-year-olds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 87 publications
5
17
0
Order By: Relevance
“…Existing evidence, albeit sparse, provides qualified support for the idea that pSES, and personality traits are related. A recent meta-analysis by Ayoub et al ( 2018 ) found that higher pSES was linked to higher offspring Openness ( r = 0.14). Associations with other personality and temperament traits were small, leading these authors to conclude that Openness is the only personality trait that shows relevant pSES-related inequality.…”
Section: Social Inequality In the Levels Of Socio-emotional Skillsmentioning
confidence: 99%
See 3 more Smart Citations
“…Existing evidence, albeit sparse, provides qualified support for the idea that pSES, and personality traits are related. A recent meta-analysis by Ayoub et al ( 2018 ) found that higher pSES was linked to higher offspring Openness ( r = 0.14). Associations with other personality and temperament traits were small, leading these authors to conclude that Openness is the only personality trait that shows relevant pSES-related inequality.…”
Section: Social Inequality In the Levels Of Socio-emotional Skillsmentioning
confidence: 99%
“…In marked contrast to the links between pSES and cognitive ability and achievement, and the links between personality and achievement, the associations between pSES and offspring personality traits have been rarely directly investigated. As Ayoub et al ( 2018 , Study 1) noted, pSES–personality links were typically not the focus of the studies summarized in their recent meta-analysis. Instead, they were only incidentally reported, for example, because pSES or personality were included as covariates in analyses with a different substantive focus.…”
Section: Social Inequality In the Levels Of Socio-emotional Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…These individuals were also considerably more likely to have been in academic difficulty at the baseline inclusion, as well as to have foreign-born parents who did not have higher-level professions. While the association of migrant status with academic difficulty is inconsistent ( Fuligni, 1997 ; Hagan et al, 2018 ), families with lower income are at greater risk for such problems ( Sirin, 2005 ; Chiu, 2007 ; Goodman et al, 2010 ; Najimi et al, 2013 ; Chittleborough et al, 2014 ; Dietrichson et al, 2017 ; Hasl et al, 2019 ). The broader role that socio-economic status plays may be both direct (through determining access to educational resources or materials, and providing means for academic support), or indirect through the lack of integration of parents into the school system where they would normally gain knowledge of its potential resources ( Sirin, 2005 ; Hill and Tyson, 2009 ; Vellymalay, 2012 ; Benner et al, 2016 ; Dietrichson et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%